2020
DOI: 10.3390/cells9092014
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Mouse Model for NASH with Advanced Fibrosis and Atherosclerosis Expressing Key Pathways of Human Pathology

Abstract: Non-alcoholic steatohepatitis (NASH) is a fast-growing liver disorder that is associated with an increased incidence of cardiovascular disease and type 2 diabetes. Animal models adequately mimicking this condition are scarce. We herein investigate whether Ldlr−/−. Leiden mice on different high-fat diets represent a suitable NASH model. Ldlr−/−. Leiden mice were fed a healthy chow diet or fed a high-fat diet (HFD) containing lard or a fast food diet (FFD) containing milk fat. Additionally, the response to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…Ldlr−/−.Leiden mice are hyperlipidemic mice that are known to develop atherosclerosis during aging, which can be aggravated by HFD feeding [15,21,22]. At the end of the current experiment mice on the chow diet had already developed severe atherosclerotic lesions in the aortic valve area, and the total lesion load was further enhanced by the HFD (Fig.…”
Section: Dietary Intervention Has Beneficial Effects On Atherosclerosis With Additive Effect When Combined With Exercisementioning
confidence: 67%
See 2 more Smart Citations
“…Ldlr−/−.Leiden mice are hyperlipidemic mice that are known to develop atherosclerosis during aging, which can be aggravated by HFD feeding [15,21,22]. At the end of the current experiment mice on the chow diet had already developed severe atherosclerotic lesions in the aortic valve area, and the total lesion load was further enhanced by the HFD (Fig.…”
Section: Dietary Intervention Has Beneficial Effects On Atherosclerosis With Additive Effect When Combined With Exercisementioning
confidence: 67%
“…Pre-existing hepatic inflammation was strongly resolved with both lifestyle interventions and almost completely blunted at the end of the study by all interventions. This is particularly noteworthy because the effects were very pronounced compared to reported pharmacological and nutritional treatments tested under similar experimental conditions [17,18,20,22,44,45]. Even hepatic fibrosis could be improved with lifestyle interventions further challenging current perception of disease management and the development of matrix remodelling anti-fibrotic pharmacotherapy strategies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Treatment with HC-24 significantly lowered the number of GR-1-positive cell aggregates in the liver, in line with the observed reduction in Cxcl1 gene and protein expression. To explore whether HC-24 affects neutrophil infiltration exclusively or has a broader effect on immune cell infiltration in general, we analysed the transcriptome dataset using previously described immune cell-type specific gene sets that allow assessment of the presence of particular leukocytes in a tissue ( 46 , 47 ). This analysis revealed that while there was an increased presence of B-cells and T-cells in HFD-fed mice relative to chow controls, this was not affected by HC-24 treatment (B-cells: HFD + vehicle vs. chow: −log(p-value) = 2.4, HFD + HC-24 vs HFD + vehicle: non-significant; T-cells: HFD + vehicle vs. chow: −log(p-value) = 2.3, HFD + HC-24 vs. HFD + vehicle: non-significant).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both tissues were subject to a comprehensive fatty acid composition analysis, including oxylipins using LC-MS/MS. Ldlr−/− Leiden mice were chosen as a model because these mice develop obesity in combination with pronounced hyperinsulinemia and adipose tissue and liver inflammation when treated with energy-dense diets for 28 weeks (to allow for the histological analysis of organ inflammation) with a human-diet-like macronutrient composition, not requiring dietary supplementation with cholesterol [ 20 , 21 , 22 , 23 ]. Under the experimental conditions employed herein, Ldlr−/− Leiden mice have been shown to develop histopathological features similar to humans and they recapitulate human disease pathways, as demonstrated by recent comparative transcriptomics, metabolomics and proteomics studies [ 21 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%